(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda is boon for mankind. Panchakarma is the most important part of Ayurveda to uproot the disease as well as achieving the perfect balance of vitiated Doshas, Dhatus and Agni. Avabahuka is a disease that affects the day to day activities like cooking, dressing, bathing, eating etc. Shoulder pain is a common clinical symptom of Avabahuka. The symptom of Avabahuka may be correlated with frozen shoulder because symptoms as well as pathogenesis are more or less similar to Avabahuka. Acharya Vangasena had mentioned Swedana Karma for Avabahuka. Aim: To evaluate the effectiveness of Jambira Pinda Sweda in the management of Avabahuka. Method: In our Panchakarma OPD 56 years old female patient came with complain of pain in the right shoulder joint and unable to perform her normal daily activities. Patient was admitted to the Panchakrma IPD of R.A.M&H and she had been treated with Jambira Pinda Sweda for 15 days. Result: After taking Panchakarma therapy, patient showed marked improvement of the symptoms like Shula (Pain), Sthambha (Stiffness) etc. Conclusion: It was found that Jambira Pinda Sweda had significant role in the management of Avabahuka.